Mood states, injury status, and countermovement jump performance in Brazilian high-level sports - Provenza de Miranda Rohlfs, I. C.; Noce, F.; Wilke, C. F.; Gabbett, T. J.; Terry, V. R.; Montenegro, A.; Assis, C. A.; Magalhães, P. M.; de Miranda, P. O., Jr.; Terry, P. C. (Sports, 2025)
This study investigated relationships between mood profiles, sports injuries, and countermovement jump with arm swing (CMJ) performance in a cohort study of 417 Brazilian athletes using a multi-methods approach during the period from January to November 2023. Six distinct mood profiles were identified, termed the shark fin (28.3%), iceberg (20.4%), submerged (18.7%), inverse iceberg (18.0%), surface (9.8%), and inverse Everest (4.8%). Athletes with the inverse Everest profile had a significantly higher risk of injury (OR = 2.90; 90% CI [1.09-7.55]) compared to those with the iceberg profile. Random forest models showed moderate predictive capability (AUC = 0.651), with vigour (12.7%) and anger (11.5%) as primary predictors. Bayesian analysis confirmed a higher injury probability in athletes with the inverse Everest profile (31.8%). Despite statistical power limitations, the results indicate that negative mood profiles, particularly those with elevated anger and fatigue, are associated with increased injury risk. Mood scores were not associated with CMJ performance variation. These findings highlight the importance of considering mood profiles in athlete monitoring systems, acknowledging the complex interplay between psychological and physical factors in injury risk.